Pre-Service Physical Education Teachers’ Playing Experience and Skill Analysis Ability - Tan, Shern Meng (JUMORA: Jurnal Moderasi Olahraga, 2024)
The relationship between playing experience and skill analysis ability among pre-service physical education teachers is understudied. This study examined the relationship between playing experience, general and game-specific, and skill analysis ability among pre-service physical education teachers in Singapore. Pre-service physical education teachers completed surveys of their playing experience and skill analysis ability prior to the start of their physical education teacher education programs. Spearman's rank-order correlations were run to determine the relationships between playing experience, general and game-specific, and skill analysis ability among pre-service physical education teachers. The results showed that the pre-service physical education teachers lacked playing experience in general and were not able to analyze any of the skills commonly taught in schools. Also, there was no correlations between playing experience and skill analysis ability, e.g., a pre-service physical education teacher with playing experience in a game/sport is unable to analyze the skills used in that game/sport, and they are also unable to analyze skills not used in that game/ sport.